Implementasi Sistem Produk Pembiayaan Mu?ârabah: Studi Faktor Turunnya Profit di Bank Muamalat Jember - Moh. Asra (Program Pascasarjana Universitas Ibrahimy, 2018)
The practice of islamic banking has been known since the time of prophet muhammad, along with his companions, because there are institutions that carry out the main functions of banking operations, which are receiving money, lending money, delivery or transfer service. This mu?ârabah financing product, is expected to be a superior product of Bank Muamalat Indonesia of Jember or at generalit bank islam. The study used a qualitative approach with focus; 1) what is the system implementation of mu?ârabah financing product at bank mu'amalat indonesia jember branch?, 2) what are the factors cause the decrease of profit in mu?ârabah financing product at bank muamalat Indonesia Jember branch? The results of the research found four factors causing the decline in profit at Bank muamalat Indonesia Jember.